2022
DOI: 10.1101/2022.01.17.476694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catch bond models may explain how force amplifies TCR signaling and antigen discrimination

Abstract: Central to T cell biology, the TCR integrates forces in its triggering process upon interaction with pMHC. Phenotypically, forces elicit TCR catch–slip bonds with strong pMHCs but slip–only bonds with weak pMHCs. While such correlation is generally observed, the quantitative bond pattern and degree of catchiness vary. We developed two models based on the structure, elastic properties, and force–induced conformational changes of the TCR–pMHC–I/II complexes to derive from their bond characteristics more intrinsi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 103 publications
(601 reference statements)
1
8
0
Order By: Relevance
“…MD simulation of protein-ligand unbinding is a notoriously difficult problem [52], as typical bond lifetimes (often ∼ 1s) are vastly longer than feasible simulation times (typically ≲1 ms). To overcome this issue, steered MD simulations, in which artificially high forces are used to increase unbinding rates, are often employed to study catch bonds [19,[36][37][38]. However, our results show that the transition state of catch bonds can be very sensitive to force; indeed, catch behavior is generated by this sensitivity.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…MD simulation of protein-ligand unbinding is a notoriously difficult problem [52], as typical bond lifetimes (often ∼ 1s) are vastly longer than feasible simulation times (typically ≲1 ms). To overcome this issue, steered MD simulations, in which artificially high forces are used to increase unbinding rates, are often employed to study catch bonds [19,[36][37][38]. However, our results show that the transition state of catch bonds can be very sensitive to force; indeed, catch behavior is generated by this sensitivity.…”
Section: Discussionmentioning
confidence: 74%
“…T-cell receptor (TCR) binding to pMHC is one exciting system where catch bonding has been observed. Intriguingly, force-induced deformations of TCRs have been suggested to play a key role in T-cell activation [38]. However, such a model would necessitate moving beyond the 2-dimensional framework used in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the acquisition of catch bonds within the TCR-pMHC interface has been shown to be a parameter that can permit differentiation between agonist from nonagonist ligands in the context of high-affinity TCR-pMHC interactions. [63][64][65] Prior work has developed models in the context of known peptides (e.g., from virus and cancer anti-gens) and TCR clones that are responsive (or not responsive) to pMHC. While these analyses do not include inflammatory arthritis (IA), we acknowledge that it is plausible that catch bonds influence T cell activation in IA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite mounting evidence that the mechanical context of antigen presentation dictates T cell activation and subsequent immune response 7,13 , the mechanisms by which mechanical forces at the synapse are sensed and transduced within the CTLs are not completely clear. Recent studies have shown that TCR can participate in the mechanosensitive activation of T cells by utilizing forces for improving the lifetime of the bond with the MHC-antigen 8,12,16,17 and by involving as yet uncharacterized downstream mechanisms at the cell surface resulting in mechanosensitivity [18][19][20] . Still, the molecular pathways downstream of TCR that consolidate and transduce the mechanical information to the cell interior remain unclear.…”
Section: Introductionmentioning
confidence: 99%